LAUNCHING A NEW JOURNAL IN THE ERA OF PUBLICATION ACCOUNTABILITY - Badar, Ahmed (Pakistan Journal of Physiology, 2005)
It was a great honor for me and my department when we were entrusted with the duty of publishing 'Pakistan Journal of Physiology' on behalf of Pakistan Physiological Society. In presence of senior and active Physiology departments of other colleges and universities, the only reason for asking us was our experience of publishing an indexed journal 'Journal of Ayub Medical College' for the last 18 years. No doubt presence of infrastructure for bringing out a journal made our task very easy, but starting anything from scratch is always a challenging task.